Pengaruh Kepribadian dan Media Sosial terhadap Tekanan Sosial Mahasiswi Tata Boga Universitas Negeri Medan dalam Menghadapi Dinamika Teknologi - Siska Asmita Sari; Elison Intropeksi Gowasa; Fatma Ingtyas Tresno; Laurena Ginting (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
The development of digital technology has changed the communication and social interaction patterns of students, especially female students. Social media not only functions as a means of self-expression, but also has the potential to increase social pressure due to exposure to beauty standards and social validation. This study aims to analyze the influence of personality and social media usage on the level of social pressure among female culinary arts students at Medan State University. The approach used was quantitative with a survey method of 170 respondents, and the data were analyzed using multiple linear regression. The results showed that personality (β = 0.314, p < 0.001) and social media usage (β = 0.630, p < 0.001) significantly influenced social pressure. Social media factors were more dominant predictors than personality. These findings emphasize the importance of strengthening digital literacy and increasing self-confidence to minimize social pressure among female students in the technological era.